2010
DOI: 10.1523/jneurosci.1425-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

LEF1/β-Catenin Complex Regulates Transcription of the Cav3.1 Calcium Channel Gene (Cacna1g) in Thalamic Neurons of the Adult Brain

Abstract: ␤-Catenin, together with LEF1/TCF transcription factors, activates genes involved in the proliferation and differentiation of neuronal precursor cells. In mature neurons, ␤-catenin participates in dendritogenesis and synaptic function as a component of the cadherin cell adhesion complex. However, the transcriptional activity of ␤-catenin in these cells remains elusive. In the present study, we found that in the adult mouse brain, ␤-catenin and LEF1 accumulate in the nuclei of neurons specifically in the thalam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
56
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 59 publications
8
56
0
1
Order By: Relevance
“…β-catenin stabilization was also restricted to adult, differentiated neurons, which are less sensitive to changes in β-catenin levels (37), and much of the available β-catenin was localized to synapses due to its association with cadherin. Finally, nuclear transport of β-catenin may also be more carefully regulated in neurons (38), and levels of Lef1 are relatively low in the hippocampus compared with other brain regions (39), reducing the sensitivity of Wnt signaling to changes in levels of cytoplasmic β-catenin (39).…”
Section: Discussionmentioning
confidence: 99%
“…β-catenin stabilization was also restricted to adult, differentiated neurons, which are less sensitive to changes in β-catenin levels (37), and much of the available β-catenin was localized to synapses due to its association with cadherin. Finally, nuclear transport of β-catenin may also be more carefully regulated in neurons (38), and levels of Lef1 are relatively low in the hippocampus compared with other brain regions (39), reducing the sensitivity of Wnt signaling to changes in levels of cytoplasmic β-catenin (39).…”
Section: Discussionmentioning
confidence: 99%
“…We and others showed that ␤-catenin is abundant in the nuclei of postmitotic thalamic neurons (23,26). The nuclear localization of ␤-catenin in mature neurons is unusual.…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, nuclear ␤-catenin was able to activate gene expression, because overexpression of AXIN2, which strongly induces ␤-catenin degradation, resulted in about 2-fold reduction of mRNA for Lef1 and Cacna1g (supplemental Fig. S1), which are known ␤-catenin targets (23).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations